Genomic diversity of SARS‐CoV‐2 in Pakistan during the fourth wave of pandemic. Issue 10 (4th July 2022) - Umair, Massab; Ikram, Aamer; Rehman, Zaira; Haider, Syed A.; Ammar, Muhammad; Badar, Nazish; Ali, Qasim; Rana, Muhammad S.; Salman, Muhammad
Abstract: The emergence of different variants of concern of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has resulted in upsurges of coronavirus disease 2019 (COVID‐19) cases around the globe. Pakistan faced the fourth wave of COVID‐19 from July to August 2021 with 314, 786 cases. To understand the genomic diversity of circulating SARS‐CoV‐2 strains during the fourth wave of the pandemic in Pakistan, this study was conducted. The samples from 140 COVID‐19‐positive patients were subjected to whole‐genome sequencing using the iSeq Sequencer by Illumina. The results showed that 97% ( n  = 136) of isolates belonged to the delta variant while three isolates belonged to alpha and only one isolate belonged to the beta variant. Among delta variant cases, 20.5% ( n  = 28) isolates were showing B.1.617.2 while 23.5% ( n  = 25), 17.59% ( n  = 19), 14.81% ( n  = 16), and 13.89% ( n  = 15) of isolates were showing AY.108, AY.43 AY.127, and AY.125 lineages, respectively. Islamabad was found to be the most affected city with 65% ( n  = 89) of delta variant cases, followed by Karachi (17%, n  = 23), and Rawalpindi (10%, n  = 14). Apart from the characteristic spike mutations (T19R, L452R, T478K, P681R, and D950N) of the delta variant, the sublineages exhibited other spike mutations as E156del, G142D, T95I, A222V, G446V, K529N, N532S, Q613H, and V483A. The phylogenetic analysis revealed the introductions from Singapore, the United Kingdom, and Germany. This study highlights the circulation of delta variants (B.1.617.2 and sublineages) during the fourth wave of pandemic in Pakistan.